Antioxidant Potential of Morinda Lucida and Psidium Guajava Extracts and Actions Against Paracetamol- Induced Kidney and Liver Injuries in Rats (American International Journal of Biology and Life Sciences, 2020)
Antioxidant agents of plants origin have continued to attract interest because of the potential they hold in the maintenance of human health accompany with their minimal side effects. The present study sought to evaluate the comparative free radical scavenging activities of ethanol extracts of air dried Morinda lucida leaves (EMLL) and Psidium guajava leaves (EPGL) by measuring their ability to scavenge 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical, nitric oxide (NOˉ) radical, 2,2 azinobis-( 3-ethylbenzothiazoline-6-sulfonic acid) (ABTS*), and inhibit lipid peroxidation (LPO). Antioxidant activities of the extracts were also determined in the plasma of the rats fed with the extracts by assaying for antiradical activity against DPPH and NO radicals in vitro. In vivo antioxidant effects of the extracts were also evaluated in paracetamol treated rats. Twenty rats were randomly divided into four groups for this study. Group 1 received normal feed as control, group 2 received 14.30mg/kg b.w of paracetamol by gavage, groups 3 and 4 received 400mg/kg b.w of EMLL and EPGL each for 7 days plus paracetamol on the 8th day respectively. Catalase (CAT) and superoxide dismutase (SOD) activities and malondialdehyde (MDA) status were assayed for in the kidney, liver and serum. Histopathological examinations of liver and kidney were also carried out. The results showed that EMLL and EPGL exhibited free radical scavenging ability in dose dependent manner towards DPPH, NO, ABTS radicals as well as inhibition of LPO. The results of evaluation of the antioxidant potentials of the extracts while in the plasma showed that they were associated with free radical scavenging activity in vivo. Paracetamol treatment caused significant (p